BRIDGING ART AND SCIENCE: THE ROLE OF BOTANICAL ILLUSTRATIONS IN PLANT TAXONOMY - Jain, Divya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Botanical illustrations have played a fundamental role in plant taxonomy by providing detailed representations of plant morphology and anatomy. This paper explores the historical evolution of botanical illustrations, from ancient herbal manuscripts to Renaissance-era scientific drawings and their influence on taxonomic classification systems like Linnaeus's binomial nomenclature. Despite the advancement of modern imaging tools and genetic analysis, traditional botanical sketches remain useful, particularly when physical specimens are unavailable. Using a qualitative research approach and comprehensive literature review, this study examines the transition of botanical illustrations from artistic expressions to essential scientific tools. It also emphasises their integration with modern imaging and molecular tools, highlighting their long-term importance in plant taxonomy.